2021
DOI: 10.1007/s10657-021-09699-1
|View full text |Cite
|
Sign up to set email alerts
|

Whistleblower rewards, false reports, and corporate fraud

Abstract: It is often claimed that rewards for whistleblowers lead to fraudulent reports, but for several US programs this has not been a major problem. We model the interaction between rewards for whistleblowers, sanctions against fraudulent reporting, judicial errors, and standards of proof in the court case on a whistleblower’s allegations and the possible follow-up for fraudulent allegations. Balancing whistleblower rewards, sanctions against fraudulent reports, and courts’ standards of proof is essential for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Such efforts hold the potential to inspire those with strong dedication to public service. Moreover, the current findings suggest that when dealing with serious misconduct such as large-scale corruption, regulatory bodies should offer commensurate rewards or other forms of compensation that adequately offset the potential risks involved in reporting (Buccirossi et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Such efforts hold the potential to inspire those with strong dedication to public service. Moreover, the current findings suggest that when dealing with serious misconduct such as large-scale corruption, regulatory bodies should offer commensurate rewards or other forms of compensation that adequately offset the potential risks involved in reporting (Buccirossi et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…This is further corroborated by the results from the supplementary analyses, which showed that perceived seriousness of wrongdoing only interacted with “monetary” rewards to predict external whistleblowing intention. In this respect, a higher reward may be seen as a necessary incentive to outweigh these risks and motivate individuals to come forward with valuable information (Buccirossi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%